Just and Civilized Humanity - Khatri, Man Bahadur (IJRDO-Journal of Applied Science, 2015)
The UK is an advanced country in education. The oldest universities like; Cambridge, Oxford, Glasgow and Durham have been also shedding a type of impression even in present situation. In the field of English Language Teaching (ELT) also it has been investing a lot of money every year. As a developed country, its rate of education, employment and investment in education is very high. Thousands of students go to the UK for higher studies and earn valuable certificates each year. But, because of open access in higher education institutions since 1990s, a number of counterfeit higher education institutions were opened till 2010/12 and collected money from the abroad students. It degraded the life of students as well as the prestige of the United Kingdom. More than a systematic development in education, it brought a type of pollution in higher education so the government of UK started making amendments in higher education policies and foreign students since 2010. So, in this study, along with lots of appreciations, I have made some comments which would be useful for both the foreign students and the government of the United Kingdom in case of education.